2015
DOI: 10.1523/jneurosci.2980-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial CD36 Contributes to Postischemic Brain Injury by Promoting Neutrophil Activation via CSF3

Abstract: The scavenger receptor CD36 is a critical factor initiating ischemic brain injury, but the cell type(s) expressing CD36 and responsible for its harmful effects remain unknown. Using bone marrow (BM) chimeras subjected to transient middle cerebral artery occlusion, we found that CD36 Ϫ/Ϫ mice transplanted with wild-type ( ¡CD36Ϫ/Ϫ mice was attenuated. Surprisingly, however, in WT¡CD36 Ϫ/Ϫ mice, in which infarcts were small, neutrophil infiltration was large and similar to that of CD36 Ϫ/Ϫ ¡WT mice, in which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Mice were transcardially perfused under deep anesthesia with 30 ml of heparinized saline to remove blood cells, as described previously (65). Briefly, cerebral hemispheres were gently triturated in HEPES-HBSS buffer and then digested with 62.5 μg/ml Liberase DH (Roche Diagnostics) and 50 U/ml DNase I (Worthington Biochemical).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were transcardially perfused under deep anesthesia with 30 ml of heparinized saline to remove blood cells, as described previously (65). Briefly, cerebral hemispheres were gently triturated in HEPES-HBSS buffer and then digested with 62.5 μg/ml Liberase DH (Roche Diagnostics) and 50 U/ml DNase I (Worthington Biochemical).…”
Section: Methodsmentioning
confidence: 99%
“…Erythrolysis was performed as described above, and afterward blood leukocytes were resuspended in buffer. Isolated brain cells and blood leukocytes were stained at 4°C with predetermined optimal concentrations of antibodies for 20 minutes and analyzed on an Accuri C6 flow cytometer (BD Biosciences) (65). For intracellular staining of CD206, cells were stained for surface markers, fixed and permeabilized using fixation and permeabilization buffers from eBioscience following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures for BM transplant have been previously described 34, 43 and are only summarized. Whole-body irradiation was performed in 7 weeks-old mice (Nordion Gammacell 40 Exactor).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic deletion and pharmacological intervention studies * This work was supported by National Institutes of Health Grants have shown that CD36 contributes to acute ischemic brain injury (18,19), apparently mediated by CD36 expressed in endothelial cells (20). On the other hand, hemorrhagic and neonatal stroke studies showed a beneficial side of CD36 through enhancing phagocytic function (21)(22)(23).…”
mentioning
confidence: 99%